2021
DOI: 10.1111/jfpp.15568
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spray drying conditions on the physical characteristics, amino acid profile, and bioactivity of blood fruit ( Haematocarpus validus Bakh.F. Ex Forman) seed protein isolate

Abstract: Proteins are macromolecules formed by amino acids that play many critical roles in human health, such as build, repair, and maintain the body's structures (Burgos-Díaz et al., 2019;Çabuk et al., 2018).Proteins can be obtained from foods derived from both plants (grains, lentils, legumes, beans, soy, peas, hemp, avocado, and nuts) and animals (fish, egg, dairy, red meat, and poultry meat) (Mokrane et al., 2010;Shaheen et al., 2016). Due to increasing vegetarianism, cardiovascular diseases, saturated fats, risk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…A significant increase in the antioxidant activity was observed when the RTS beverage was sonicated at 40°C (585.78 μmol TE/100 ml) but with the increase in treatment temperature, a significant loss was observed, thus indicating the loss of antioxidants like ascorbic acid and phenolics due to exposure to high treatment temperatures (524.21 μmol TE/100 ml). Similar changes in the antioxidant activity with increasing temperature and the kind of treatment were reported by Sasikumar, Das, and Deka (2020), Sasikumar, Vivek, and Jaiswal (2021). Higher treatment temperatures ensure the microbial safety of products but at the cost of nutritional components.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…A significant increase in the antioxidant activity was observed when the RTS beverage was sonicated at 40°C (585.78 μmol TE/100 ml) but with the increase in treatment temperature, a significant loss was observed, thus indicating the loss of antioxidants like ascorbic acid and phenolics due to exposure to high treatment temperatures (524.21 μmol TE/100 ml). Similar changes in the antioxidant activity with increasing temperature and the kind of treatment were reported by Sasikumar, Das, and Deka (2020), Sasikumar, Vivek, and Jaiswal (2021). Higher treatment temperatures ensure the microbial safety of products but at the cost of nutritional components.…”
Section: Resultssupporting
confidence: 84%
“…With a further increase in temperature (46-52°C), AA values reduced significantly as compared to the values corresponding to the previous mild heat treatment. Sasikumar, Vivek, and Jaiswal (2021) also reported a significant loss in AA when RTS beverage was treated with conventional pasteurization as compared to sonication at mild temperatures and concluded that the chemical decomposition of AA might have occurred at higher treatment temperatures.…”
Section: Physicochemical Characteristics Of Blood Fruit Rts Beveragementioning
confidence: 99%
See 1 more Smart Citation
“…From bioactive compounds retention, the resulting powder obtained at high inlet and outlet air temperatures and low homogenization rate demonstrated a higher value for both total and surface phenolic contents, and antioxidant activity [71,102]. However, products without incorporation of carrier have a higher agglomeration tendency, which can reduce their direct exposure to the air and protect the bioactive compounds from deterioration [113,[116][117].…”
Section: Common Characteristics Of Spray Drying Productsmentioning
confidence: 99%
“…An elevated drying temperature may induce an enhanced oxidation in the spray drying of lipophilic core constituents, such as polyunsaturated fatty acids and cubosome [115,118]. In the course of spray drying, when the particle temperature increases beyond a certain level (depending on the nature of the protein), the tertiary structure of protein begins to disintegrate and gradually alters the secondary structure [117]. In addition, micron size droplets leaving the atomizer also potentially suffer from high interfacial stresses caused by a very high surface area to volume ratio.…”
Section: Common Characteristics Of Spray Drying Productsmentioning
confidence: 99%